Molecular cloning and expression analysis of interferon regulatory factor-1 (IRF-1) of turbot and sea bream - Ordás, M. Camino; Abollo, Elvira; Costa, M. M.; Figueras Huerta, Antonio; Novoa, Beatriz (Molecular Immunology, 2006)
9 páginas, 4 figuras, 1 tabla The interferon regulatory factor (IRF) family comprises transcription factors that regulate the expression of interferon and interferon-related cytokines. Using the RACE technique, we have determined the complete cDNA sequence of turbot (Scophthalmus maximus) and sea bream (Sparus aurata) IRFs. These sequences shared characteristics with other IRFs of fish, mammals and birds, and showed high similarity with IRF-1. Indeed, they were included in the IRF-1 cluster of the phylogenetic tree constructed with IRF-1 and IRF-2 sequences of several organisms, and presented a low number of basic amino acid residues in the carboxy-terminal end of the proteins. All of these characteristics led to the identification of turbot and sea bream IRFs as IRF-1. Two IRF-1 sequences were obtained for both turbot and sea bream, and we named them turbot/sea bream IRF-1a and IRF-1b. Turbot IRF-1a differed from turbot IRF-1b in four nucleotides. The presence of both IRF types in cDNA from 45 turbot livers was determined by RFLP, suggesting the duplication of the gene. Sea bream IRF-1b presented a deletion of 121 bp in its ORF compared to sea bream IRF-1a, and since both IRF types were present in all 25 cDNAs analyzed by PCR, we hypothesized that the truncated sea bream IRF-1b was probably an alternative splicing product. Turbot and sea bream IRF-1 expression was constitutive in every analyzed organ, as reported before for other fish species. Poly I:C significantly stimulated turbot IRF-1 expression in muscle, spleen and kidney 24 h post-treatment, while viral haemorrhagic septicemia virus (VHSV) induced a differential expression of this factor in kidney 8 h after infection. These results do not agree with those previously reported for flounder and trout IRF. Other expression experiments with turbot leukocytes stimulated in vitro with poly I:C and with brain and kidney of sea bream infected with nodavirus did not bring out differential IRF expression levels in stimulated samples with respect to controls ...